Multipotential use of an old drug, as a new solution for anticancer therapy and multidrug-resistant urinary tract infections - Patryk Banaś; Kamila Abram; Justyna Adamus; Jakub Rafał Pierzchała; Katarzyna Bednarz; Natalia Sobańska; Aleksandra Paulina Banasiak; Rafał Teichman; Jakub Kasprowicz; Michał Hyjek (Kazimierz Wielki University, 2023)
Introduction        Nitroxoline (NTX) is a well-known chemotherapeutic agent that has been used to treat urinary tract infections since the 1960s. Today, the incidence of multidrug-resistant (MDR) bacterial strains is on the rise worldwide. This has resulted in repurposing, whereby during the ongoing research on nitroxoline, the possibility of its wide use has been demonstrated, not only in treatment against resistant pathogens, but also potential broad anti-cancer applications. Aim of the study The purpose of our work was to review scientific articles and show the multi-potential - anti-pathogenic and anti-tumor use of nitroxoline. Methods and materials We reviewed the English-language literature in the PubMed database, using the key words: "Nitroxoline", "Nitroxoline cancer", "Nitroxoline antibacterial use"   Results Analysis of studies has shown that nitroxoline, currently used in benign urinary tract infections, is also applicable in the treatment of urinary tract infections caused by multidrug-resistant bacteria (MRD). It is also active against drug-resistant fungi and mycobacteria. Repurposing has also demonstrated the anticancer effects of nitroxoline through inhibition proliferation, induction apoptosis of tumor cells and other mechanisms, making it likely that nitroxoline will be used in cancer treatment regimens in the future. Conclusion Nitroxoline has found widespread use in the treatment of urinary tract infections caused by multidrug-resistant bacteria (MRD) and by strains of resistant fungi, which in today's world are spreading and increasing their drug resistance. Repurposing has shown promising anticancer activity of nitroxoline in the treatment of urinary tract cancers and more. The data supporting the effects of nitroxoline seem promising, suggesting the rationale for future clinical trials to further our understanding of the exact mechanisms of action and use of nitroxoline in oncology treatment.